2015
DOI: 10.1007/s00170-015-7457-8
|View full text |Cite
|
Sign up to set email alerts
|

The modified firefly algorithm considering fireflies’ visual range and its application in assembly sequences planning

Abstract: This paper proposes a modified discrete firefly algorithm (MDFA) to solve the problem of assembly sequence planning. Firstly, to improve the performance of the firefly algorithm (FA), we proposed a MDFA by endowing the fireflies with the capability of changeable visual range. The computing case shows the proposed algorithm is more effective and robust than standard FA, genetic algorithm and particle swarm optimization algorithm. Secondly, a method of how to set parameters for FA and MDFA is proposed. This meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The first one is using the same updating formula and changing the results to discrete values afterwards [82,94,104]. And the second is to modify the updating formula on the discrete space [97][98][99][100][101]. The first problem is susceptible of trapping in local solution and misses the optimal solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one is using the same updating formula and changing the results to discrete values afterwards [82,94,104]. And the second is to modify the updating formula on the discrete space [97][98][99][100][101]. The first problem is susceptible of trapping in local solution and misses the optimal solution.…”
Section: Discussionmentioning
confidence: 99%
“…Another modification in this category is proposed in [101]. The decision variables, x i 's, represent assembly sequence.…”
Section: 5itrmentioning
confidence: 99%
“…In this section, we introduce an assembly model which takes some important assembly factors into account, including the geometric constraints, the stability of assembly, the changes of assembly direction, the assembly tool changes, and the process precedence. In the next section, a brief introduction of this model is presented, and for more detail you can found it in Zeng et al [33] and Li et al [34].…”
Section: Assembly Modelingmentioning
confidence: 99%
“…A sequence violating the precedence process rule demands extra fixtures and more skilled workers. For this reason, the APPR matrix T is defined by Li et al [34] to represent the assembly process precedence of a mechanical product, shown as Eq. 3.…”
Section: Precedence Analysis Of the Assembly Processmentioning
confidence: 99%
“…The main objective is to enhance the design life of components such as box type heat exchangers and radiators. Furthermore, the PSO and FFA are also applied to optimize suitable process parameters that yield better tensile strength [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%